Delay to Attendance for Elective Surgery: Analysis of Individual and Organizational Factors at Hospital Islam Sakinah Mojokerto - Sulis Diana; Roisul Umam; Dhonna Anggreni; Fitria Edni Wari (Universitas STRADA Indonesia, 2024)
Background: Poor service quality will cause waste of time and resources, increase errors in service implementation and the risk of other. Purpose: The Purpose of this study was to examine the influence of individual and organizational factors on the delay in the presence of doctors and nurses in elective surgery. Method: This research is quantitative, sample is 49 nurses and doctors. An instrument for obtaining data from questionnaires. The independent variables are individual factors and organizational factors, the dependent variable is late attendance. Place of research: Sakinah Islamic Hospital in Mojokerto, statistical test using logistic regression. Results: The results of the study obtained the results of individual factors, namely attitudes and personality that influenced the delay in the presence of doctors and nurses in elective surgery. The factors of understanding of instructions, quality of interaction, confidence, personal responsibility, and closeness of authority figures do not affect the delay in the presence of doctors and nurses in elective surgery. Organizational factors in the form of location status affect the delay in the presence of doctors and nurses in elective surgery while other factors, namely supervision, peer support, legitimacy of authority figures, and authority figure status do not affect the delay in the presence of doctors and nurses in elective surgery. Conclusion: Individual factors, namely attitudes, and personality, affect the delay in the presence of doctors and nurses in elective surgery. Organizational factors in the form of location status affect the delay in the presence of doctors and nurses in elective surgery.